New Species of Osedax (Siboglinidae: Annelida) from New Zealand and the Gulf of Mexico - Berman, Gabriella H.; Hiley, Avery S.; Read, Geoffrey B.; Rouse, Greg W. (Zootaxa, 2024)
Osedax is now known to be distributed around the world with more than 30 named and undescribed species. Here we report the discovery of four new species from two localities: Osedax bozoi n. sp. and Osedax craigmcclaini n. sp. from the Gulf of Mexico and Osedax estcourti n. sp. and Osedax traceyae n. sp. from off New Zealand. Osedax bozoi n. sp., Osedax estcourti n. sp., and Osedax traceyae n. sp. belong to Clade II within Osedax, one of the nude palp or apinnulate clades. Osedax craigmcclaini n. sp. belongs to the pinnulate palp Clade V. This study relies primarily on phylogenetic analysis, with some morphological analysis. Genetic data clearly show that the four new species are distinctive from their closest Osedax relatives. Two of the new species were found from less than 400 m depth, and incidences of shallower water Osedax in Clade II are shown here for the first time.